2003
DOI: 10.1101/lm.50703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Enrichment on Spatial Memory and Neurochemistry in Middle-Aged Mice

Abstract: The present study compared the effects of environmental enrichment on spatial memory, glutamic acid decarboxylase (GAD) activity, and synaptophysin levels in middle-aged male and female mice. Prior to testing, a subset of 18-month-old male and female C57BL/6 mice was housed with two to three toys and a running wheel in the home cage for up to 29 d. Adult mice (7 mo) of both sexes and the remaining middle-aged mice were group (social) housed, but not exposed to enriching objects. After the enrichment period, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 69 publications
5
100
2
5
Order By: Relevance
“…During this period, the onset of senescence is highly dependent on age, sex, species and strains (Frick et al, 2003;Hebda-Bauer et al, 2007). Since environmental factors and life style also play a key role in the progression of ageing, middle-aged models potentially display measurable reactivity to environmental challenges and may be a useful tool for toxicological investigations (Frick et al, 2003;Hebda-Bauer et al, 2007;Kohman et al, 2010).…”
Section: Middle-aged Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, the onset of senescence is highly dependent on age, sex, species and strains (Frick et al, 2003;Hebda-Bauer et al, 2007). Since environmental factors and life style also play a key role in the progression of ageing, middle-aged models potentially display measurable reactivity to environmental challenges and may be a useful tool for toxicological investigations (Frick et al, 2003;Hebda-Bauer et al, 2007;Kohman et al, 2010).…”
Section: Middle-aged Modelmentioning
confidence: 99%
“…Indeed, middle-aged biological systems are particularly sensitive to toxicological factors, as shown by exacerbated behavioral impairments in middle-aged animals, when compared to younger animals, in response to lipopolysaccharide administration and traumatic brain injury (Hoane et al, 2004;Kohman et al, 2010). In addition, enrichment or self food-restriction diet during middle-age may postpone the appearance of age-related memory decline and neurochemical modifications (Frick et al, 2003;Kollen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Controls are group (social) or singly (isolated) housed and not exposed to enriching objects. Recent work has shown that enrichment improves hippocampal-dependent memory and enhances hippocampal morphology and plasticity in young-adult (Davis, Jones & Derrick, 2004;Duffy, Craddock & Nguyen, 2001;Kempermann, Kuhn & Gage, 1997;Rampon, Tang, Goodhouse, Shimizu, Kyin & Tsien, 2000), middle-aged (Frick, Stearns, Pan & Berger-Sweeney, 2003;Kempermann, Kuhn & Gage, 1998), and aged (Frick et al, 2002;Nakamura, Kobayashi, Ohashi & Ando, 1999;Soffié, Hahn, Terao & Eclancher, 1999;Winocur, 1998) rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…While some found significant positive effects on spatial memory only in aged mice 7 , other studies also demonstrated such effects in middle-aged mice 6 . Still, some studies have reported improvement on spatial task execution by both young and young adult mice groups 8,9,10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, those studies with significant results in relation to spatial memory, despite using similar enrichment protocols, maintained the EE for longer periods, from 2 to 21 months 9,10,12 . Some of the groups that reported significant results with an EE period and enrichment protocol similar to this study 6,7,8 evaluated middle-aged and aged mice.…”
Section: Discussionmentioning
confidence: 99%